“Death Is a Mercy”: The American Monomyth of the Superhero in 2005’s The Punisher Video Game - Mariano Falzone (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
Debuting in 1974, the creation of Marvel Comics’ character of the Punisher was influenced by vigilante violence fiction, such as Don Pendleton’s The Executioner book series (1969 onwards). In the early 2000s, the character had a resurgence in popularity, kickstarted by the critically acclaimed comic book run from Garth Ennis, Steve Dillon and other collaborators. This popularity reached its peak in 2004 with the release of The Punisher, a film directed by Jonathan Hensleigh and starring Thomas Jane. The following year, a video game of the same name was released by the studio Volition, which saw Jane reprising the title role and Ennis being credited as co-writer. After a brief history of the character’s creation and its first high point of transmedia popularity in the late 1980s and early 1990s, this article analyses the media texts of the Punisher between 2000 and 2005, culminating in Volition’s video game. To do so, I will draw on the conceptual framework developed by John Shelton Lawrence and Robert Jewett in The Myth of the American Superhero (2002), specifically the urban vigilante variant of that myth, as well as the transmedia interplay between the Punisher texts. While Garth Ennis’ comics from the early 2000s comment on the mythic paradigm in a postmodern way and may even criticise the processes on which it operates, the 2004 film and the 2005 video game reinforce it.